Investment protection and regulatory sovereignty in outer space - Güneş Ünüvar (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2025)
The rise of commercial space ventures heightens tensions between investor protections and states' regulatory sovereignty. With dual-use technologies and evolving space law, balancing innovation, security, and sustainability is critical. Coordinated global frameworks and well-grounded national policies are vital to align investment treaties with outer space governance.
Keywords: 330